2022
DOI: 10.3390/molecules27175720
|View full text |Cite
|
Sign up to set email alerts
|

6-Formyl Umbelliferone, a Furanocoumarin from Angelica decursiva L., Inhibits Key Diabetes-Related Enzymes and Advanced Glycation End-Product Formation

Abstract: Over the years, great attention has been paid to coumarin derivatives, a set of versatile molecules that exhibit a wide variety of biological activities and have few toxic side effects. In this study, we investigated the antidiabetic potential of 6-formyl umbelliferone (6-FU), a novel furanocoumarin isolated from Angelica decursiva. Numerous pharmacological activities of 6-FU have been previously reported; however, the mechanism of its antidiabetic activity is unknown. Therefore, we examined the action of 6-FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The amount of fructosamine that was present promoted the formation of AGEs, suggesting that prunin functions to effectively lower fructosamine concentrations and mitigate some of the difficulties linked to AGEs. Numerous naturally occurring compounds can prevent the synthesis of fructosamine, according to several studies, ,,, but ours is the first to demonstrate that prunin suppresses the levels of fructosamine formation.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The amount of fructosamine that was present promoted the formation of AGEs, suggesting that prunin functions to effectively lower fructosamine concentrations and mitigate some of the difficulties linked to AGEs. Numerous naturally occurring compounds can prevent the synthesis of fructosamine, according to several studies, ,,, but ours is the first to demonstrate that prunin suppresses the levels of fructosamine formation.…”
Section: Resultsmentioning
confidence: 57%
“…Usually, Arg and Lys were the primary predicted glycation sites in the protein, and the glycation of the protein was greatly influenced by the properties of its surrounding amino acids. , According to other studies, Ile, Leu, Phe, and Arg may greatly boost Lys’s reactivity in a variety of compounds containing Lys. , According to this study, the interactions between prunin and HSA involving the amino acids Ile, Leu, Lys, and Arg may have reduced the glycosylation activity of nearby potential glycation sites. It has previously been reported that a variety of small molecules, such as luteolin, ursonic acid, 6-formyl umbelliferone urolithin A, chrysin, and luteolin, , form hydrophobic and hydrogen bonding interactions with Arg, Leu, Val, Lys, Tyr, and Pro in HSA, thereby promoting HSA stability and inhibiting the formation of AGEs and glycation. Similar residue-binding properties were shown by prunin in this study, which may increase the stability of HSA and inhibit glycation and the production of AGE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the docking analysis to investigate the binding poses of compounds inside the active receptor pockets, the crystal protein structures for PTP1B (PDB ID: 1NNY for the catalytic site; 1T49 for the allosteric site) and α-glucosidase (PDB ID: 3A4A) were downloaded from the Protein Data Bank (PDB) [ 53 ]. These protein structures were confirmed using X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…This information cannot be considered complete and needs additional study of the componential profile and quantification data of L. officinale coumarins. Additionally, furanocoumarins are bioactive metabolites with proven antivirus [ 40 ], antiallergic [ 41 ], antidiabetic [ 42 ], antidepressive [ 43 ], anticancer [ 44 ], and anti-inflammatory potential [ 45 ]. Thus, furanocoumarin-containing foods may be promising functional products.…”
Section: Introductionmentioning
confidence: 99%